Studi Cara Pandang Perempuan Dalam Film Charlie’s Angels - Andika Kartika Sari (Universitas Nasional, 2022)
Film is a medium for delivering messages through moving images. However, often in film narratives, there is a point of view of the dominance of male characters as subjects and active characters while women as passive characters or objects. Thus, women are often seen as a group that is vulnerable to violence, both sexual and symbolic violence. This article aimed to find a woman's point of view in Charlie's Angels, where women are seen as the dominant subject and not a vulnerable group. This research employed a descriptive-qualitative research method with primary and secondary data sources. The primary data was the Charlie's Angels film, while the secondary data was supporting documents such as books and articles. Data collection techniques employed documentation techniques. The data analysis technique applied Roland Barthes Semiotics to find denotations, connotations, and myths in film scenes to explore their meaning. In addition, this study used Tseelon's theory which states that in the film, there is a woman's point of view that rejects the notion that women are considered sexual objects formed from the point of view of men. The results of this study indicated that the Charlie's Angels film transparently applied a female perspective, made women's roles more dominant than men's, and negated the concept of women as sexual objects from the male point of viewFilm merupakan media penyampai pesan melalui gambar bergerak. Namun, sering kali dalam narasi film, terdapat sudut pandang dominasi tokoh laki-laki sebagai subjek dan tokoh aktif, sementara perempuan sebagai tokoh pasif atau objek. Sehingga, perempuan seringkali dipandang sebagai kelompok yang rentan dengan kekerasan, baik kekerasan seksual maupun simbolik. Artikel ini bertujuan menemukan sudut pandang perempuan dalam film Charlie’s Angels yang mana perempuan dipandang sebagai subjek yang dominan dan bukanlah kelompok yang rentan. Penelitian ini menggunakan metode penelitian deskriptif-kualitatif dengan sumber data primer dan sekunder. Data primer yang digunakan ialah film Charlie’s Angels, sedangkan data sekunder berupa dokumen pendukung, seperti buku penunjang dan artikel. Teknik pengumpulan data menggunakan teknik dokumentasi. Teknik analisis data menggunakan Semiotika Roland Barthes untuk menemukan denotasi, konotasi, mitos dalam adegan-adegan film dalam teks, sehingga dapat digali maknanya. Selain itu, penelitian ini menggunakan teori Tseelon yang menyatakan jika dalam film terdapat sudut pandang perempuan yang menolak adanya kepercayaan jika perempuan dianggap sebagai objek seksual yang dibentuk berdasar sudut pandang laki–laki. Hasil penelitian ini menunjukkan bahwa film Charlie’s Angels secara transparan menggunakan perspektif perempuan dan membuat peran perempuan menjadi lebih dominan daripada laki-laki, serta meniadakan konsep perempuan sebagai objek seksual dari sudut pandang laki-laki.